Group cognitive behavioural interventions for low back pain in primary care: extended follow-up of the Back Skills Training Trial (ISRCTN54717854). - Lamb, S; Mistry, D; Lall, R; Hansen, Z; Evans, D; Withers, E; Underwood, MR (2012)
Group cognitive behavioural intervention (CBI) is effective in reducing low back pain and disability over a 12-month period, in comparison to best practice advice in primary care. The aim was to study the effects of this CBI beyond 12 months. We undertook an extended follow-up of our original randomised, controlled trial of a group CBI and best practice advice in primary care, in comparison to best practice advice alone. Participants were mailed a questionnaire including measures of disability, pain, health services resource use, and health-related quality of life. The time of extended follow-up ranged between 20 and 50 months (mean 34 months). Fifty-six percent (395 of 701) of the original cohort provided extended follow-up. Those who responded were older and had less disability and pain at baseline than did the original trial cohort. After 12 months, the improvements in pain and disability observed with CBI were sustained. For disability measures, the treatment difference in favour of CBI persisted (mean difference 1.3 Roland and Morris Disability Questionnaire points, 95% confidence interval 0.27 to 2.26; 5.5 Modified von Korff Scale disability points, 95% confidence interval 0.27 to 10.64). There was no between-group difference in Modified von Korff Scale pain outcomes. The results suggest that the effects of a group CBI are maintained up to an average of 34 months. Although pain improves in response to best practice advice, longer-term recovery of disability remains substantially less.